Moment Equations in Modeling a Stable Foreign Currency Exchange Market in Conditions of Uncertainty - Josef Diblík; Irada Dzhalladova; Mária Michalková; Miroslava Růžičková (Abstract and Applied Analysis)
The paper develops a mathematical model of foreign currency exchange market in the form of a stochastic linear differential equation with coefficients depending on a semi-Markov process. The boundaries of the domain of its instability is determined by using moment equations.